2010
DOI: 10.1080/1556035x.2010.523345
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Factors in Group Psychotherapy: A Study of Egyptian Drug Addicts

Abstract: The effect of group therapy on substance-dependent patients has been demonstrated in several studies emphasizing the costeffectiveness of this intervention. However, little research was conducted on how group therapy can help these patients. The objective of this article is to study the therapeutic factors of group therapy among a group of substance-dependent patients and to study the relation between the therapeutic factors of group therapy with these patients and clinical outcome of relapse or continuing abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 12 publications
2
29
0
1
Order By: Relevance
“…Additionally, our hypothesis was confirmed because patients engaged in therapeutic modality IV reported significantly better results in terms of abstinence than those who had attended in any of the other treatment modalities, consistent with literature previously discussed 14,18 . In general, in the area of mental health, empirical evidence has shown that treatment protocols which include group therapy, particularly cognitive behavioral therapy, are more effective compared to other treatment modalities 12,18 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, our hypothesis was confirmed because patients engaged in therapeutic modality IV reported significantly better results in terms of abstinence than those who had attended in any of the other treatment modalities, consistent with literature previously discussed 14,18 . In general, in the area of mental health, empirical evidence has shown that treatment protocols which include group therapy, particularly cognitive behavioral therapy, are more effective compared to other treatment modalities 12,18 .…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, group therapy also provides social, emotional, and relational skills in order to increase their perception of being accepted and accept others, as well as dealing with emotional states in the relationship with others 13 . Some factors that arise from the group therapy include catharsis, cohesion, interpersonal learning 14 , affiliation, confrontation, support, gratification, and identification, which seem to promote the involvement of patients in their treatment 5,15 , and promote a better prognosis 16 . These factors promoted by group therapy increase the success of interventions, not only in the addiction problems, but also in psychotherapy in general 17 .…”
Section: Introductionmentioning
confidence: 99%
“…These factors were noted to be the cognitive, behavioral, and emotional aspects of change process in psychotherapy. Catharsis, insight, interpersonal learning and cohesion were valued above the remaining factors (5,6,7). These four factors were suggested to be inclusive of the other factors (8).…”
Section: Introductionmentioning
confidence: 99%
“…developmental causes of their behavior), or unconscious (4). Yalom suggested actual change took place when patients gained insight via here and now in therapy (5). Along with existential factors, insight and catharsis were the most valued therapeutic factors in group psychotherapy for inpatients with alcohol dependence difficulties (24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation